Effects of antiplatelet therapy after stroke due to intracerebral haemorrhage (RESTART): are neurologists feeling more comfortable to RESTART antiplatelet? - Girotra, Tarun; Feng, Wuwei (Annals of Translational Medicine, 2019)
With an aging global population, the prevalence of chronic atherosclerotic diseases requiring antithrombotic medications has risen steadily (1). The worldwide incidence of haemorrhagic strokes has also been on the rise, as indicated by the Global burden of disease (GBD) study, which revealed a 47% increase in the absolute number of haemorrhagic strokes (2).